A Decade Trends in The Development of Ethnoscience-Integrated Learning Media: A Systematic Review of Challenges and Opportunities in Science Education (2017–2026) - Sura Juddin; Gesti Maharani; ⁠Nada Clairina Sophian (Indonesian Publication Center, 2026)
This study aims to analyze the decade-long trend in the development of ethnoscience-integrated learning media in science education from 2017 to 2026, as well as to identify the challenges and opportunities for their development. The study is grounded in the need for more contextual science learning by integrating scientific knowledge with local wisdom. This research employs a descriptive bibliometric method, using data sourced from Google Scholar, which were analyzed with Publish or Perish and Dimension.ai software and visualized with VOSviewer. A total of 1,000 scientific documents were analyzed to map publication trends, keywords, and the relationships among research topics. The results indicate a significant increase in the number of publications, with a dominance of development-based research (R&D) focusing on learning media such as student worksheets (LKPD) and instructional modules. However, the research remains largely localized and has not been optimally integrated with advanced technologies. In addition, contributions to theoretical development and long-term impact evaluation are still limited. These findings suggest that although ethnoscience has great potential in science education, there is a need to strengthen technological integration, global collaboration, and shift the focus from product development toward evaluating learning outcomes.